Why Britain should leave Ireland - Connolly Association, CA (1979)
Pamphlet reproducing statements given at a press conference, held at the Ivanhoe Hotel, Bloomsbury, London, on 12 December 1979 by Michael Mullen (General Secretary of the Irish Transport and General Workers' Union), Anthony Coughlan, (President of the Irish Sovereignty Movement), the Reverend Terence McCaughey and Daltun O Ceallaigh, (Secretary of the Irish Sovereignty Movement and Information Officer of the Irish Transport and General Workers' Union).